'The biggest car crash in NHS history': the media portrayal of GP pay before and after the introduction of the Health and Social Care Bill 2011. Issue 1 (17th October 2016) - Balkham, Adam; Alderson, Sarah
Abstract : Background: The introduction of the Health and Social Care Bill (2011) changed the role of GPs to include commissioning of health services. Aim: This study aimed to identify any differences in the media portrayal of GPs before and after the introduction of the Bill. Methods: We retrospectively searched four British newspapers over the period 2009–2013 using the media database Nexis. In order to directly compare the findings of the study with the work of Tanner et al ., articles relating to GP pay were analysed using thematic analysis. Themes were identified and each article was scored to determine whether it portrayed GPs positively or negatively. Results: GPs were portrayed slightly less negatively after the introduction of the Bill. The theme of 'high salaries' persisted despite reference to 'pay freezes'. References to decreased trust in the patient–doctor relationship appeared after the introduction of the Bill. Conclusion: Negative portrayal of GP pay has continued and a lack of trust in GPs has started to be portrayed. This trend may exacerbate the low morale amongst the profession and difficulties in recruiting and retaining GPs.